A sociodemographic, clinical study of patients with venous ulcer - Abbade, L P F; Lastoria, S.; Rollo, H. D.; Stolf, Hamilton Ometto [UNESP] (Blackwell Publishing, 2005)
Background Venous ulcer is the most serious consequence of chronic venous insufficiency and is responsible for almost 70% of chronic leg ulcers. The main purpose of this research was to describe social, demographic and clinical characteristics of patients with venous ulcers and to identify some professional repercussions of this pathology.Subjects and methods We evaluated patients with a clinical picture compatible with venous ulcer. The sociodemographic characteristics of the patients, and the clinical characteristics and professional repercussions of the pathology were studied. We used the ankle-brachial index to identify associated arterial disease. The body mass index (BMI) was used for the classification of the nutritional condition of the patients.Results A total of 120 patients were included in the study (90 females and 30 males; 80.8% White; 44.2% > 60 years old). Ninety-one per cent of the patients had been in education for less than 4 years, and 89.7% were on the poverty line. Thirty-five per cent were retired, 2.5% were receiving government help due to disease and 4.2% were unemployed. About 16% of patients were out of work due to the disease, and 49.2% presented some degree of disability in terms of work tasks. The ulcer area was less than 30 cm(2) in 69.1% of patients. The first ulcer episode occurred in 13.4 years on average, and 64.2% of patients had recurrent episodes. Females presented on average 5.65 pregnancies, and 75.4% of patients were overweight.Conclusion Venous ulcer occurred mainly in the low-income population, who presented with little formal education. Generally, the ulcers were present for a long time and were recurrent, with repercussions for the capabilities of patients to work.